Desbravando os infernos de John Constantine na revista Hellblazer (1988-1991) - Assis, Carlos Henrique de Castro (2016)
The goal of this work is to analyze and understand the constitutive process of the stories published in the comic book Hellblazer during the years of 1988 and 1991, as well as the creation of the stories protagonist, wizard John Constantine, and part of the themes approached by these comics during this period. The creation of the character John Constantine and the stories of its first phase of publications are the result of the combined work of English writers and the USA publishing company DC Comics. This production is perceived here as a criticism to the neoliberal conjuncture that England was going through during the years of Margareth Thatcher s government. One of the aspects analyzed in this work is how the experience of these English writers was articulated in their unique creations, thus expanding the possibilities of the language used in comic books and of themes approached in this type of publication. Another aspect that is analyzed in this work is how these themes are inserted and their viability in the USA comic book industry. Based on the youth experiences of the generation born post the Second World War, which would be most of the British cartoonists that entered in the USA market in the 1980 s, the English youth s disbelief in the 1960 s and early 1970 s utopias is analyzed. The purpose of this analysis is to understand the pessimism and the disbelief that appear in the stories scripted by Jamie Delano. Following this, and based on Delano s demonstrated interest in William S. Burroughs, evidences of the roles that marginalized and devious individuals take in stories published at Hellblazer are analyzed. Lastly, this research seeks to understand how the city points the issues of the conjuncture in which the comic book was published, since the city in Hellblazer is represented as a territory that is constituted by antagonist interests, in which the tensions become present